Lost in Transition: The Long and Winding Road Toward Epilepsy Surgery-An Analysis of Obstacles Prior to Surgery and Call for Orchestrated Health Care Efforts in Epilepsy - Kasper, Burkhard; Graf, Wolfgang; Sharma, Sunjay; Kasper, Ekkehard M. (Journal of Pediatric Neurology, 2020)
Difficult-to-treat epilepsy is defined as ongoing seizures despite adequate pharmacological treatment. This condition is affecting a significant percentage of epilepsy patients and is estimated to be as high as one-third of all patients. Epilepsy surgery, targeting the removal of the key parts of cerebral convolutions responsible for seizure generation and often including a structural lesion, can be a very successful approach. However, this necessitates careful patient selection by comprehensive investigations, proving the localization of the epileptogenic zone as well as measures to make such surgeries safe. With careful selection as a prerequisite, the percentage of patients achieving seizure freedom by neurosurgical intervention is high, approximating two-thirds of all epilepsy surgeries performed. In contrast, the average duration of a patient's pharmacoresistant focal epilepsy prior to surgery anywhere around the globe is around 20 years. Given that typical patients are similar to 30 to 40 years of age at the time of surgery, many patients have been living with chronic seizures since childhood or adolescence. This means that most of these patients have been going through several stages of medical care for years or even decades, both as children and adults, without ever being fully investigated and/or selected for surgery which is concerning. Yet, there is no set standard for a timeline leading toward successful surgery in epilepsy. It is obvious that the average transit period from the moment of first seizure manifestation until the day of successful surgery takes much too long. This is the reason why we see these patients lost in transition.
CRIS-Team WoS Importer:2020-09-04